2022
DOI: 10.1159/000524289
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Release Calcifediol Effectively Raises Serum Total 25-Hydroxyvitamin D Even in Overweight Nondialysis Chronic Kidney Disease Patients with Secondary Hyperparathyroidism

Abstract: <b><i>Introduction:</i></b> Obesity increases the risk of vitamin D insufficiency, which exacerbates secondary hyperparathyroidism in chronic kidney disease. Recent studies suggest that serum total 25-hydroxyvitamin D (25OHD) levels of ≥50 ng/mL are necessary to produce significant reductions in elevated parathyroid hormone levels in nondialysis patients. Data from real-world and randomized controlled trials (RCTs) involving these patients were examined for (1) relationships between vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…An inverse relationship has been consistently observed in the absence of CKD between serum 25OHD and both body weight and BMI [27–31] . Observations of this relationship have been recently extended to include patients with stage 3–5 CKD [32] and indicate that obesity limits the effectiveness of cholecalciferol and ergocalciferol to treat SHPT.…”
Section: Discussionmentioning
confidence: 99%
“…An inverse relationship has been consistently observed in the absence of CKD between serum 25OHD and both body weight and BMI [27–31] . Observations of this relationship have been recently extended to include patients with stage 3–5 CKD [32] and indicate that obesity limits the effectiveness of cholecalciferol and ergocalciferol to treat SHPT.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of PTH lowering with AVD was surprising and possibly due to routine prescription of insufficient dosages without up-titration, but was expected with NVD, as numerous meta-analyses [4,[16][17][18][19][20] have concluded that PTH lowering with cholecalciferol or ergocalciferol supplements is unproven and clinically insignificant. NVD has been shown to be less effective in raising serum 25D in overweight patients [25,26] and most CKD patients are overweight, developing kidney disease from hypertension or type 2 diabetes, both common complicaitons of obesity. Disparities in PTH-lowering efficacy in this study were not related to differences in the bioavailabilities of the various treatments, as ERC has a slow-release formulation with only 25% bioavailabilty [23] compared to substantially higher bioavailabities reported for AVD and NVD [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…11 Hepatic 25-hydroxylase activity is reduced in both obesity 12 and CKD, 13 slowing the intended elevation of serum total 25D. 14 In contrast, immediate-release calcidiol (IRC) rapidly produces peak serum 25D levels (at approximately 6 h), 15 requires no hepatic activation, is more water soluble, and travels in mesenteric lymph bound to DBP (not in chylomicrons). 7 It is stored, contrary to the Panel's conclusion, in serum bound to DBP, which reduces its accumulation in adipose tissue, muscle and liver and enables its circulation to the kidney and to other tissues containing the 1a-hydroxylase (CYP27B1) for both endocrine and intracrine conversion to calcitriol, respectively.…”
Section: 'Vitamin D (Either Ergocalciferol or Cholecalciferolmentioning
confidence: 99%